Marketing Mix Affected to Decision Making of Consumer About Optician’s Services in Western Region of Thailand - Watcharamaneekun, Narasnan (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The Study was “the marketing mix affected to the decision making of consumer about the optician’s services in western region of Thailand”. The purpose study were (1) to study the marketing mix affect the decision making of the consumer enter to use services of the optician’s in western region of Thailand. 2) to compare the decision making of the consumer enter to use services of the optician’s in western region of Thailand distinguish by the demographic of the optician and 3) to analyze the relationship between the optician’s behavior about the marketing mix (7Ps) affected to decision making of Consumer and the decision making of the consumer enter to use services of optician’s in western region of Thailand. The sample sizes composed of 400 persons who the optician’s enter to services of the Optician’s in western region of Thailand. The instrument collected the data by questionnaires which had 0.929 confidence values by the cronbach alpha coefficient and 1.00 Index of item objective congruence. The statistics analyzed the data such as percentage, mean, standard deviation, one-way analyses of variances, Pearson’s product moment correlation coefficient and multiple regression analysis by the level statistical significant at .05 was valuable specification. The results of this study was the marketing mix about consumer behavior in use services of the optician’s were “much” level and found that the mostly consumer were decision for use services of the optician’s at “much” level also. As for the hypothesis testing found that the difference monthly income factors was different decision making used services of the optician’s in overall at .05 significant level. The separate consideration in each aspect found that the difference demographic of the opticians such as gender factors were different decision making used services on the need recognition aspects at .05 significant levels. The difference educational factors were different decision making used services on buying decision makings aspect and behavior after decision makings aspect at .05 significant levels and found that the difference monthly income and occupation factors were different decision making used services on behavior after decision makings aspect at .05 significant levels. Meanwhile, the optician’s behavior about marketing mix (7Ps) affected to decision making of consumer all 7 aspects were relationship with the decision making of the consumer enter to use services in overall and every aspects at .05 significant level and found that the optician’s behavior about marketing mix (7Ps) such as the product aspects and the process aspects and the physical evidence and presentation aspect were influence to the decision making of the optician’s at .05 significant level. Article history : Accepted 2 June 2015 SIMILARITY INDEX = 0.00